Potential of Mangrove Forest Tourism with A4 (Attraction, Amenity, Accessibility, Ancillary) in Kulu Village, Wori District North Sulawesi Indonesia - Devitra V. Lampongayo; Takaendengan, Mita Erdiaty; Fonny Sangari (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purpose: Minahasa Utara has now become one of the continuously developing regions thanks to the ongoing construction, especially due to its status as a Special Economic Zone (SEZ). The Likupang SEZ is expected to become the center of regional economic growth, thereby positively impacting the surrounding areas, including Kulu Village located in North Minahasa Regency, North Sulawesi, which has various natural tourism potentials that have not yet been fully utilized. Some of them include captivating diving and snorkeling spots, exotic mangrove forests, and Paniki Island, which holds a wealth of local ecosystems and culture. The development of tourist attractions is directed as a mainstay sector to drive economic growth, increase local revenue, expand job opportunities, and enhance the recognition and marketing of products in order to boost the tourism industry. Kulu Village in Wori District, which has an area of mangrove forest, beautiful sea views, and cool air, makes it a good location for a tourist destination. With the conduct of this research, the potential of the Mangrove Forest Tourism can be known by many people and can be visited by tourists. Research method: The method used involves direct observation in the field with the managers of the Mangrove Forest Tourism to understand the potential it possesses as well as the available facilities. Data analysis conducted based on the 4A. (Attraction, Accessibility, Amenity, Anciallary). Result and dicussion: The results of this study indicate that mangrove forest tourism has the potential to become a leading tourist attraction in North Minahasa, supported by existing facilities and good management. Accessibility that can be reached even though the road conditions are good enough to be traversed by two vehicles at the same time. Amenities available at the Mangrove Forest Tourism site include gazebos, restaurants, and a mini café with a fairly complete menu. And the support from the local government and the North Minahasa Regency Tourism Office. Overall, the Mangrove Forest Tourism in Kulu Village has great potential as an attractive and sustainable ecotourism destination if it continues to be well-managed and supported by adequate infrastructure. Implication: The implications are ecological preservation, the benefits of mangrove forests for the surrounding economic development, and cultural empowerment through sustainable planning. The challenges also include limited infrastructure, environmental risks, and accessibility gaps. Addressing these issues encourages balanced development and community engagement.